1939
DOI: 10.1037/h0057798
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the Porteus maze test.

Abstract: An article in the October 1937 issue of the JOURNAL OF EDUCA-TIONAL PSYCHOLOGY by Moshe Brill 1 reported some work done with the Porteus Maze, the subjects being one hundred inmates of the State Colony for Feebleminded Males at New Lisbon, N. J. According to the author, the group consisted of "fifty socially well-adjusted and fifty seriously maladjusted mentally deficient boys." Brill found that the maladjusted boys scored higher, on the average, than the well-adjusted.On the basis of these results he conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1941
1941
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Brill (15), in a study of fifty socially well-adjusted and fifty seriously maladjusted mentally deficient boys, found that the maladjusted boys scored higher on the average than the well adjusted and concluded that earlier statements as to the validity of the test in measuring social adaptation were not fully justified. In reply, Porteus (55) pointed out that Brill's interpretation of feeble-mindedness was not in accordance with accepted standards and cited further evidence to indicate the validity of the test as a measure of the subject's prudence and planning capacity. In addition, Porteus emphasized that the maze test is a supplement to and not a substitute for the Binet.…”
Section: Studies and Discussion Of Performance Testsmentioning
confidence: 89%
“…Brill (15), in a study of fifty socially well-adjusted and fifty seriously maladjusted mentally deficient boys, found that the maladjusted boys scored higher on the average than the well adjusted and concluded that earlier statements as to the validity of the test in measuring social adaptation were not fully justified. In reply, Porteus (55) pointed out that Brill's interpretation of feeble-mindedness was not in accordance with accepted standards and cited further evidence to indicate the validity of the test as a measure of the subject's prudence and planning capacity. In addition, Porteus emphasized that the maze test is a supplement to and not a substitute for the Binet.…”
Section: Studies and Discussion Of Performance Testsmentioning
confidence: 89%
“…Erikson and Roberts (1971) found the TQs of two groups of delinquents to be over 15 points higher than their Binet, Wechsler Adult Intelligence Scale (WAIS), or Wechsler Intelligence Scale for Children (WISC) IQs. Grajales (1945), Porteus (1939), Shakow and Millard (1935), and Wright (1944) all reported mean maze scores that were within 3 points of the re-ported mean IQ test scores, and out of four comparisons, TQ was higher than IQ in three. Jarrett (1926), on the other hand, stated that none of the 100 delinquents in his study had a maze TA higher than his Binet MA.…”
Section: Historical Developmentmentioning
confidence: 93%
“…Quantitative Score (TA or TQ) A reanalysis of maze TA's ability to identify delinquents was undertaken to assess the utility of this approach. Although it was originally believed that the relationship believed to exist among TA, intelligence, and social adjustment would be of use in identifying delinquents, it is clear from the data available on delinquent groups that there is no consistent relationship between TA and intelligence within these groups (Erikson & Roberts, 1966;Erikson & Roberts, 1971;Grajales, 1945;Jarrett, 1926;Porteus, 1939;Shakow & Millard, 193S;Wright, 1944). Erikson and Roberts (1966) found the mean TQs (using the old norms) of two delinquent groups to be over 20 points higher than their mean IQs as measured by the California Short-Form Test of Mental Maturity.…”
Section: Historical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that examined the validity of the PMT and the ability to evaluate social adaptation, maze ratings were examined alongside Stanford-Binet performance. The rank order correlations were 0.57 for the Binet and 0.77 for the maze test (18). The PMT was adapted to Turkish by Togrol (19).…”
Section: Porteus Maze Testmentioning
confidence: 99%